Growth and Color Brightness of Glofish Fed Natural and Artificial Diets In Cianjur District, West Java Province - Rostika, Rita; Hari Priowirjanto, Gatot; Zidni, Irfan; Mustika Dewi, Aisah (Green Publisher Indonesia, 2024)
It is known that natural feed, in addition to being preferred because it moves, also has dyes that make the color of ornamental fish more contrasting than artificial feed. The purpose of this study is to find out which type of natural feed (Silk Worm (Tubifex sp.), Daphnia sp., Frozen Blood Worm) and artificial feed, which is more effective against the growth and brightness of the color of Glofish Starfire Red, which will be carried out in August 2024-October 2024 in Cianjur Regency, West Java Province. The study was conducted using an experimental method using a Complete Random Design (RAL) with 4 treatments and 3 replicates. The treatment given is as follows: A (Research using natural feed Daphnia sp, B (Research using natural feed Bloodwarm/Chironomidae, C (Research using natural feed Tubifex sp), D (Research using artificial feed). The parameters observed were Absolute Length Growth, Absolute Weight Growth, Specific Growth Rate and Color Brightness, to analyze the color brightness of Starfire Red fish using https://redketchup.io color comparison.